Flat Foot berdasarkan Clark’s Angle dan Indeks Massa Tubuh pada Remaja Usia 11 – 13 Tahun - Hidayati, Nitaya Putri Nur; Ramadhani, Raihan Putri (Politeknik Kesehatan Kemenkes Surakarta, 2025)
Background: Body mass index is an indicator used to determine a person's body composition, its relation to nutritional status. An imbalance in nutritional intake in the body can result in abnormal BMI values ​​in the form of overweight to obesity. Being overweight in children over a long period of time can result in certain deformities in the feet, one of which is flat foot. Objectives: This study examined the relationship between flat foot that measuring using Clarke’s Angle and Body Mass Index. Methods: This study used an Observational analytic design with a cross-sectional method. The subjects who met the inclusion and exclusion criteria. Each subject had their body mass index measured and a foot print test. Flat foot is measured using the footprint test with the Clarke's angle parameter. The correlation test used to test between variables is the Spearman test. Results: 265 samples meeting inclusion criteria, most flat foot cases occurred in males. A total of 36 research subjects were overweight, evenly between females and males. Spearmen test analysis indicated a highly significant p=0,001 (p<0,05), suggesting a significant relationship between flat foot and overweight. Conclusion: Flat foot that measuring using Clarkes’s angle had a significant relationship with overwight. Keywords: Flat foot; Body Mass Index, Adolescence